P-510 Impact of ART on quality of life in predicted hyper-responders: conventional IVF versus in-vitro maturation of oocytes. (30th June 2022) - Mostinckx, L; Sanmartín, V; Agirregoitia Marcos, E; Mackens, S; Boudry, L; Roelens, C; Agirregoitia Marcos, N; De Vos, M
Abstract: Study question: Do in-vitro maturation (IVM) of oocytes and conventional IVF (cIVF) have different effects on quality of life (QoL) in women with polycystic ovaries (PCO)? Summary answer: Women with PCO who have IVM treatment experienced a lower impact on QoL compared to their counterparts who underwent cIVF. What is known already: While studies in predicted hyper-responders have shown that success rates of IVM are lower compared to cIVF, cIVF is associated with more hormonal side effects and complications including OHSS. According to a recent discrete choice experiment among hyper-responders in the Netherlands, not only success rates may play a role in these women's preferences for fertility treatment, but also projected risks, burden, and costs. It is currently unknown whether the increased efficiency of cIVF in hyper-responders may come at the expense of impact on QoL and whether IVM may be associated with a lower impact on mental health parameters. Study design, size, duration: This is a single-centre, observational prospective study including 149 women with polycystic ovaries on ultrasound scan who had their first cycle of IVM (n = 75) or cIVF (n = 74) in a tertiary referral hospital. Patients were included between May 2017 and March 2021. Participants/materials, setting, methods: Patients <37 years embarking on ART with their partner were asked to complete the Hospital Anxiety and Depression Scale (HADS) and the Fertility Quality of Life Questionnaire (FertiQoL) at three timepoints: intake at the fertility clinic (T1), at oocyte retrieval (T2) and after the first cycle outcome was known (T3). The primary objective was to determine the impact of ART on QoL. Statistical analysis included descriptive statistics and the use of general linear models. Main results and the role of chance: In total, 124/149 (83.2%) patients completed questionnaires at two timepoints and 97/149 (65.1%) patients returned complete questionnaires. Mean age (28.92 ± 3.48y vs. 30.63 ± 3.23y, p = 0.003) was different in both groups. BMI (25.76 ± 5.81kg/m2 vs. 24.25 ± 4.83kg/m2, p = 0.089) and duration of infertility (27.12 ± 18.31 months vs. 31.00 ± 20.14 months, p = 0.270) were similar in IVM and cIVF patients, respectively. The distribution of PCOS phenotypes A, B, C and D, and PCOM was comparable in both groups (p = 0.142). Univariable analysis showed that women undergoing cIVF had worse side effects scores at T2 than women who had IVM (5.09 ± 3.24 vs. 3.08 ± 2.43, p < 0.001). According to multivariable ANOVA, the impact of IVM on anxiety and depression scores was similar to that of cIVF. Patients undergoing IVM had better scores for the FertiQol Subscale for Treatment Tolerability (68.54 ± 16.75 vs. 59.09 ± 22.68, p = 0.011), suggesting that cIVF caused more mental symptoms and daily life disruption. The Relational Subscale at T3 indicated that IVM patients suffered less impairment of sexuality and communication. Finally, social interactions at T3 were more severely affected by cIVF than IVM based on the social FertiQoL subscale (74.57 ± 19.64 vs 66.96 ± 17.60, p = 0.039). Limitations, reasons for caution: The type of ART was not assigned randomly, thus selection bias was highly likely because of the study design. The willingness to trade off chance of pregnancy for lower burden and risks may have influenced the choice of ART type and may have modulated susceptibility to impact on QoL. Wider implications of the findings: Patients utilizing IVM may expect fewer side effects, more tolerability to treatment and less impact on their relationship and social life compared to those who opt for cIVF. Lower efficiency may be an acceptable trade-off for the benefits of IVM. These findings should be corroborated by an RCT. Trial registration number: clinical trials.gov NCT03066349